Altered Anterior Segment Biometric Parameters in Mice Deficient in SPARC - Ho, Henrietta (2017)
Purpose: Secreted protein acidic and rich in cysteine (SPARC) and Hevin are structurally related matricellular proteins involved in extracellular matrix assembly. In this study, we compared the anterior chamber biometric parameters and iris collagen properties in SPARC-, Hevin- and SPARC-/Hevin-null with wild-type (WT) mice. Methods: The right eyes of 53 WT, 35 SPARC-, 56 Hevin-, and 63 SPARC-/Hevin-null mice were imaged using the RTVue-100 Fourier-domain optical coherence tomography system. The parameters measured were anterior chamber depth (ACD), trabecular-iris space area (TISA), angle opening distance (AOD), and pupil diameter. Biometric data were analyzed using analysis of covariance and adjusted for age, sex, and pupil diameter. Expression of Col1a1, Col8a1, and Col8a2 transcripts in the irises was measured by quantitative polymerase chain reaction. Collagen fibril thickness was evaluated by transmission electron microscopy. Results: Mice that were SPARC- and SPARC-/Hevin-null had 1.28- and 1.25-fold deeper ACD, 1.45- and 1.53-fold larger TISA, as well as 1.42- and 1.51-fold wider AOD than WT, respectively. These measurements were not significantly different between SPARC- and SPARC-/Hevin-null mice. The SPARC-null iris expressed lower Col1a1, but higher Col8a1 and Col8a2 transcripts compared with WT. Collagen fibrils in the SPARC- and SPARC-/Hevin-null irises were 1.5- and 1.7-fold thinner than WT, respectively. The Hevin-null iris did not differ from WT in these collagen properties. Conclusions: SPARC-null mice have deeper anterior chamber as well as wider drainage angles compared with WT. Therefore, SPARC plays a key role in influencing the spatial organization of the anterior segment, potentially via modulation of collagen properties, while Hevin is not likely to be involved.